Being a Social Worker in Social Services during the Covid-19 Pandemic: a Spanish Case Study - Paéz-Izquierdo, Virginia; Muriel-Saiz, Mercedes (Acciones e Investigaciones Sociales, 2022)
Covid-19 has led to a health, social and economic crisis, the like of which has never been seen before. The world has had to tackle a new reality that has shaken the most basic structures of our system. In Spain the Social Services have been declared essential services but, even so, the social workers interviewed in this study have not perceived that this has translated into greater support for the system or for their work. This article forms part of a national funded research project that has developed the only tool to monitor the impact of Covid-19 on the Social Services in Spain. Its sampling design has made it possible to carry out 164 telephone interviews at 52 public Social Services centres all over Spain.The aim of this article is to ascertain the effects of the pandemic on the daily practice of social work through the analysis of professional discourse, and also to discuss the impact of Covid-19 with special attention to issues such as the irruption of telematics, the emotional exhaustion of professional teams or the new forms of reorganisation of the Social Services. In other words, changes in the organisational dynamics of the centres, in the incorporation of telematics, in interpersonal relations between the work teams, etc. Changes that will all be decisive in predicting the course of social change in the Social Services in the coming years.
Keywords: Social work, Social Services, social intervention, pandemic, Spanish case